Artificial intelligence chatbot for gold-based Islamic financial education in Indonesia - Muhammad Muchson (Asian Journal Collaboration of Social Environmental and Education, 2026)
Background: Islamic financial literacy related to gold-based products in Indonesia remains relatively low, particularly in understanding sharia-compliant gold pawn (rahn emas), investment mechanisms, and trust in digital financial services. This gap in literacy limits community financial resilience and poses a challenge to sustainable social development. While digital platforms such as Pegadaian Digital have expanded access to Islamic financial products, limited public understanding and skepticism toward digital services continue to hinder optimal utilization within the broader social context. This study aims to evaluate the effectiveness of an AI-based chatbot, designed with a specific instructional persona to enhance user engagement, as an educational tool for gold-based Islamic finance. Methods: A quantitative pretest–posttest design was employed involving 30 participants who interacted with the chatbot. Learning outcomes were measured using 12 multiple-choice questions covering four aspects: understanding of gold pawn mechanisms, sharia principles, interest in gold investment, and trust in digital financial services. Findings: The results indicate a substantial improvement in participants’ knowledge after using the chatbot. The average score increased from 52.8% in the pretest to 85.6% in the post-test. Conclusion: These findings suggest that AI chatbots are effective, scalable, and accessible tools for enhancing Islamic financial literacy, but also serve as a novel intersection between technological innovation and social empowerment. By bridging the literacy gap, this technology contributes to a more stable and resilient social-financial environment in Indonesia. Novelty/Originality of this article: The novelty of this study lies in the integration of an Agentic RAG architecture with a supportive Sharia-consultant persona, which not only ensures factual accuracy based on DSN-MUI fatwas but also addresses the socio-cognitive barriers of rural learners. The greatest improvement was observed in understanding sharia principles and digital service security, which are critical components for fostering digital trust within the community.